"Trivial" Cysts Redefine the Risk of Cancer in Presumed Branch-Duct Intraductal Papillary Mucinous Neoplasms of the Pancreas: A Potential Target for Follow-Up Discontinuation?. (October 2019) - Marchegiani, Giovanni; Andrianello, Stefano; Pollini, Tommaso; Caravati, Andrea; Biancotto, Marco; Secchettin, Erica; Bonamini, Deborah; Malleo, Giuseppe; Bassi, Claudio; Salvia, Roberto
Abstract : OBJECTIVES: The management of small and incidental branch duct intraductal papillary mucinous neoplasms (BD-IPMNs) still is of concern. The aim is assessing the safety of a surveillance protocol through the evaluation of their progression to malignancy. METHODS: All presumed BD-IPMNs observed from 2000 to 2016 were included. Only patients presenting without worrisome features (WFs) and high-risk stigmata (HRS) at diagnosis were included. Development of WF, HRS, pancreatic cancer (PC), and survival were analyzed. BD-IPMNs were defined as trivial in the continuing absence of WF/HRS after 5 years of surveillance. The age-specific standardized incidence ratio of PC in the general population was used for comparison. RESULTS: A total of 1, 036 BD-IPMNs without WF/HRS at diagnosis were included, 4.2% developed WF or HRS, and 1.1% developed PC after a median of 62 months. The median cyst growth rate was 0 mm/yr. A growth rate ≥2.5 mm/yr and the development of WF resulted independent predictors of PC. The standardized incidence ratio of PC for trivial BD-IPMN (n = 378) was 22.45 (95% confidence interval 8.19–48.86), but considering only patients aged >65 years (n = 198), it decreased to 3.84 (95% confidence interval 0.77–11.20). DISCUSSION: Surveillance of the vast majority of presumed BD-IPMNs is safe, as the risk of PC is comparable to postoperative mortality of pancreatic surgery. A growth rate ≥2.5 mm/yr is the main predictor of PC, reinforcing the role of repeated observations. A trivial BD-IPMN in patients aged >65 years might not increase the risk of developing PC compared with general population, identifying potential targets for follow-up discontinuation.